A combined grain scale elastic–plastic criterion for identification of fatigue crack initiation sites in a twin containing polycrystalline nickel-base superalloy. (15th January 2016) - Stinville, J.C.; Lenthe, W.C.; Miao, J.; Pollock, T.M.
Abstract: Damage initiation during cycling loading of polycrystalline metallic alloys involves localized damage at the scale of individual grains. To better understand damage processes and to build models for material behavior, there is a need for quantitative assessment of the microstructural configurations that favor fatigue crack initiation. In materials that form annealing twins during processing, these special interfaces are often locations of particular interest for their role in strain and damage accumulation. In the present study, fatigue experiments in the very high and low cycle fatigue regime on a René 88DT polycrystalline nickel-base superalloy were performed to statistically evaluate grain-scale features that favor crack initiation. Combined elastic and plastic criteria at the grain scale have been developed. A crack distribution function is defined to compare and assess the effect of the microstructural parameters for the two fatigue regimes. Graphical abstract: